A High‐Throughput Mass Spectrometric Enzyme Activity Assay Enabling the Discovery of Cytochrome P450 Biocatalysts. Issue 30 (13th June 2019) - de Rond, Tristan; Gao, Jian; Zargar, Amin; de Raad, Markus; Cunha, Jack; Northen, Trent R.; Keasling, Jay D.
Abstract: Assaying for enzymatic activity is a persistent bottleneck in biocatalyst and drug development. Existing high‐throughput assays for enzyme activity tend to be applicable only to a narrow range of biochemical transformations, whereas universal enzyme characterization methods usually require chromatography to determine substrate turnover, greatly diminishing throughput. We present an enzyme activity assay that allows the high‐throughput mass‐spectrometric detection of enzyme activity in complex matrices without the need for a chromatographic step. This technology, which we call probing enzymes with click‐assisted NIMS (PECAN), can detect the activity of medically and biocatalytically significant cytochrome P450s in cell lysate, microsomes, and bacteria. Using this approach, a cytochrome P450BM3 mutant library was successfully screened for the ability to catalyze the oxidation of the sesquiterpene valencene. Abstract : Easy as pecan pie : A high‐throughput enzyme assay was developed, based on a combination of click chemistry, fluorous affinity purification, and nanostructure‐initiator mass spectrometry. The utility of the technique, called PECAN, was demonstrated by screening a library of cytochrome P450s for activity on valencene.